RESEARCH OF COMMUNICATION QUALITY WITH WI-FI TECHNOLOGY DEPENDING ON THE NATURE OBSTACLES - Конахович, Г.; Пасічник, В.; Хомяк, В.; Тищук, С.; Кичигіна, М. (Science-based technologies, 2011)
Researches of signal-to-noise in the spread of radiowave technology Wi-Fi in the presence obstacle of differentnature. Presented universal recommendations for the effective deployment of WiFi network indoors.